Sites of international memory - Sluga, Glenda 1962-; Darian-Smith, Kate 1961-; Herren-Oesch, Madeleine 1956- (University of Pennsylvania Press, 2023)
"Sites of International Memory interrogates the political and cultural legacies of the recent international past in conceptualizations of nationhood and identity today in the material and ideological sites of international memory. It maps an international past that was often simultaneously imperial and national, cosmopolitan and global, and that is now is sometimes self-consciously remembered, or more often actively forgotten."
Keywords: Geschichte; Nationalbewusstsein; Kollektives Gedächtnis; Collective memory; History, Modern / 20th century; Internationalism / History / 20th century; Memorialization / International cooperation; Aufsatzsammlung